Gender-Specific Independent and Combined Effects of the Cortisol-to-Cortisone Ratio and 11-Deoxycortisol on Prediabetes and Type 2 Diabetes Mellitus: From the Henan Rural Cohort Study - Xue Liu; Jingjing Jiang; Xiaotian Liu; Zhicheng Luo; Yan Wang; Xiaokang Dong; Dandan Wei; Wenqian Huo; Songcheng Yu; Linlin Li; Shuna Jin; Chongjian Wang; et al. (Journal of Diabetes Research)
Objective. The aim of the study was to investigate the independent and combined effects of the cortisol-to-cortisone ratio (F/E) and 11-deoxycortisol on prediabetes and type 2 diabetes mellitus (T2DM) among different genders. Methods. A case-control study was performed including 2676 participants from the Henan Rural Cohort Study. Liquid chromatography-tandem mass spectrometry was used to assess serum cortisol, cortisone, and 11-deoxycortisol. Conditional logistic regression was performed to estimate the associations between hormones and outcomes. Results. After adjusting for multiple variables, the negative associations of F/E and 11-dexyocortisol with T2DM were observed in females (T3 vs. T1: OR=0.56, 95% CI: 0.39-0.80 for F/E; T3 vs. T1: OR=0.44, 95% CI: 0.27-0.73 for 11-dexyocortisol). However, only 11-dexyocortisol showed a negative association with prediabetes both in males and females. Compared with the combination of low F/E and 11-dexyocortisol, the combination of middle F/E and high 11-dexyocortisol was significantly associated with prediabetes (OR=0.29, 95% CI: 0.12-0.71) in males. Furthermore, the combination of high F/E and 11-dexyocortisol was associated with the lowest odds of prediabetes (OR=0.39, 95% CI: 0.21-0.73) and T2DM (OR=0.25, 95% CI: 0.12-0.52) in females. Conclusions. Serum F/E level was negatively associated with T2DM only in females whereas serum 11-deoxycortisol level was negatively associated with prediabetes in males and with prediabetes and T2DM in females. Additionally, their combination has a synergistic effect on T2DM.